Breakthrough SARS-CoV-2 infections with the delta (B.1.617.2) variant in vaccinated patients with immune-mediated inflammatory diseases using immunosuppressants: a substudy of two prospective cohort studies. (June 2022) - Boekel, Laura; Stalman, Eileen W; Wieske, Luuk; Hooijberg, Femke; van Dam, Koos P J; Besten, Yaëlle R; Kummer, Laura Y L; Steenhuis, Maurice; van Kempen, Zoé L E; Killestein, Joep; Volkers, Adriaan G; Tas, Sander W; et al.
Summary: Background: Concerns have been raised regarding the risks of SARS-CoV-2 breakthrough infections in vaccinated patients with immune-mediated inflammatory diseases treated with immunosuppressants, but clinical data on breakthrough infections are still scarce. The primary objective of this study was to compare the incidence and severity of SARS-CoV-2 breakthrough infections between patients with immune-mediated inflammatory diseases using immunosuppressants, and controls (patients with immune-mediated inflammatory diseases not taking immunosuppressants and healthy controls) who had received full COVID-19 vaccinations. The secondary objective was to explore determinants of breakthrough infections of the delta (B.1.617.2) variant of SARS-CoV-2, including humoral immune responses after vaccination. Methods: In this substudy, we pooled data collected in two large ongoing prospective multicentre cohort studies conducted in the Netherlands (Target to-B! [T2B!] study and Amsterdam Rheumatology Center COVID [ARC-COVID] study). Both studies recruited adult patients (age ≥18 years) with immune-mediated inflammatory diseases and healthy controls. We sourced clinical data from standardised electronic case record forms, digital questionnaires, and medical files. We only included individuals who were vaccinated against SARS-CoV-2. For T2B!, participants were recruited between Feb 2 and Aug 1, 2021, and for ARC-COVID, participants were recruited between April 26, 2020, and March 1, 2021. In this study we assessed data on breakthrough infections collected between July 1 and Dec 15, 2021, a period in which the delta SARS-CoV-2 variant was the dominant variant in the Netherlands. We defined a SARS-CoV-2 breakthrough infection as a PCR-confirmed or antigen test-confirmed SARS-CoV-2 infection that occurred at least 14 days after vaccination. All breakthrough infections during this period were assumed to be due to the delta variant due to its dominance during the study period. We analysed post-vaccination serum samples for anti-receptor binding domain (RBD) antibodies to assess the humoral vaccination response (T2B! study only) and anti-nucleocapsid antibodies to identify asymptomatic breakthrough infections (ARC-COVID study only). We used multivariable logistic regression analyses to explore potential clinical and humoral determinants associated with the odds of breakthrough infections. The T2B! study is registered with the Dutch Trial Register, Trial ID NL8900, and the ARC-COVID study is registered with Dutch Trial Register, trial ID NL8513. Findings: We included 3207 patients with immune-mediated inflammatory diseases who receive immunosuppressants, and 1807 controls (985 patients with immune-mediated inflammatory disease not on immunosuppressants and 822 healthy controls). Among patients receiving immunosuppressants, mean age was 53 years (SD 14), 2042 (64%) of 3207 were female and 1165 (36%) were male; among patients not receiving immunosuppressants, mean age was 54 years (SD 14), 598 (61%) of 985 were female and 387 (39%) were male; and among healthy controls, mean age was 57 years (SD 13), 549 (67%) of 822 were female and 273 (33%) were male. The cumulative incidence of PCR-test or antigen-test confirmed SARS-CoV-2 breakthrough infections was similar in patients on immunosuppressants (148 of 3207; 4·6% [95% CI 3·9–5·4]), patients not on immunosuppressants (52 of 985; 5·3% [95% CI 4·0–6·9]), and healthy controls (33 of 822; 4·0% [95% CI 2·8–5·6]). There was no difference in the odds of breakthrough infection for patients with immune-mediate inflammatory disease on immunosuppressants versus combined controls (ie, patients not on immunosuppressants and healthy controls; adjusted odds ratio 0·88 [95% CI 0·66–1·18]). Seroconversion after vaccination (odds ratio 0·58 [95% CI 0·34–0·98]; T2B! cohort only) and SARS-CoV-2 infection before vaccination (0·34 [0·18–0·56]) were associated with a lower odds of breakthrough infections. Interpretation: The incidence and severity of SARS-CoV-2 breakthrough infections in patients with immune-mediated inflammatory diseases on immunosuppressants was similar to that in controls. However, caution might still be warranted for those on anti-CD20 therapy and those with traditional risk factors. Funding: ZonMw (the Netherlands Organization for Health Research and Development) and Reade foundation.